Effects of Tangibility, Reliability, Responsiveness, Assurance, Empathy, Corporate Image, and Core Benefits on Customer Satisfaction - Fitri Balango; Hananiel M. Gunawan (International Journal of Economics Accounting and Management, 2026)
This study aims to analyze the effect of Tangibility, Reliability, Responsiveness, Assurance, Empathy, Corporate Image, and Core Hotel Benefit on Customer Satisfaction among guests of Aston Manado Hotel. The research employs a quantitative approach, with data collected through questionnaires distributed to 100 respondents who are hotel guests. The data obtained were analyzed using the SmartPLS method. The independent variables in this study include Tangibility, Reliability, Responsiveness, Assurance, Empathy, Corporate Image, and Core Hotel Benefit, while Customer Satisfaction serves as the dependent variable. The results of this study indicate that, overall, the independent variables have a significant effect on improving customer satisfaction. This study implies that enhancing service quality covering Tangibility, Reliability, Responsiveness, Assurance, Empathy, Corporate Image, and Core Hotel Benefit is crucial in creating customer satisfaction. Furthermore, the findings suggest that consistent service quality aligned with guest needs can enhance the overall stay experience and strengthen guest loyalty at Aston Manado Hotel